2012
DOI: 10.2527/jas.2011-4031
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for osteochondrosis in French Trotter horses1

Abstract: A genome-wide association study for osteochondrosis (OC) in French Trotter horses was carried out to detect QTL using genotype data from the Illumina EquineSNP50 BeadChip assay. Analysis data came from 161 sire families of French Trotter horses with 525 progeny and family sizes ranging from 1 to 20. Genotypes were available for progeny (n = 525) and sires with at least 2 progeny (n = 98). Radiographic data were obtained from progeny using at least 10 views to reveal OC. All radiographic findings were described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 32 publications
4
64
0
2
Order By: Relevance
“…Therefore, it is possible that some of the polymorphisms reported as significant represent false positive hits. The same problem has already been reported by other authors (Lykkjen et al 2010;Teyssèdre et al 2010). Because of the relatively low heritability of the trait, SNP (and corresponding genes) of very high effects on the occurrence of OCD are not expected.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, it is possible that some of the polymorphisms reported as significant represent false positive hits. The same problem has already been reported by other authors (Lykkjen et al 2010;Teyssèdre et al 2010). Because of the relatively low heritability of the trait, SNP (and corresponding genes) of very high effects on the occurrence of OCD are not expected.…”
Section: Resultssupporting
confidence: 64%
“…Different SNP were also found for cold blooded horses by Distl (2013). A French study identified osteochondrosis associated SNP on ECA03, ECA13, ECA14, ECA15 for the Standardbred Trotter (Teyssèdre et al 2010), whereas a Norwegian study found corresponding SNP on ECA05, ECA10, ECA27, and ECA28 (Lykkjen et al 2010). Breeds may differ in the linkage disequilibrium (Corbin et al 2012), but it is expected that breed-specific results will be more compatible.…”
Section: Introductionmentioning
confidence: 99%
“…The closest to BIEC2-799865 was presented recently in a pre-print version of a study carried out in French Trotters and is located at 100-110Mb (Teyssèdre et al 2011). The relatively close proximity of the two QTL represents some correspondence between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Three previous GWAS for OC in the horse have also identified QTL on ECA3 (Komm 2010;Lampe 2009;Teyssèdre et al 2010). The closest to BIEC2-799865 was presented recently in a pre-print version of a study carried out in French Trotters and is located at 100-110Mb (Teyssèdre et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation